PERENCANAAN MANAJEMEN KONSTRUKSI PADA STRUKTUR GEDUNG MALL PELAYANAN PUBLIK DI KABUPATEN BENGKAYANG: PERENCANAAN MANAJEMEN KONSTRUKSI PADA STRUKTUR GEDUNG MALL PELAYANAN PUBLIK DI KABUPATEN BENGKAYANG - Syamsa, Grandhis Hizbullah; Pala Guna, Dayu; Sarpawi, Sarpawi (Jurusan Teknik Sipil Polnep, 2024)
The author carried out construction management planning for the Public Service Mall building in Bengkayang Regency. Therefore, to realize the construction of the Public Service Mall Building, appropriate construction management planning is required, so that results are obtained that comply with the requirements.Therefore, the author plans a good construction project management system in an effort to expedite the construction of the Public Service Mall Building which is the title of this Final Assignment. The method used in discussing construction management is a management system for costs, quality, time, Human Resources (HR) and Occupational Safety and Health in work structures which include foundations, beams, columns, stairs and floor plates. Based on the results of the method analysis, it was found that the cost of preparing the work and structures required to complete the Public Service Mall Building project was IDR. 11.147.075.000,00 and can be completed within 26 weeks or 200 calendar days. For quality planning in the form of a quality checklist table. In Human Resources (HR) planning in the form of the number of labor requirements as a means for carrying out good work and in K3 management planning the plan is in the form of control and control of potential K3 hazards for each type of work for the need for PPE and APK. Keywords: Planning, construction management, public service mall